The Diversity Decline in Wild and Managed Honey Bee Populations Urges for an Integrated Conservation Approach - Panziera, Delphine; Requier, Fabrice; Chantawannakul, Panuwan; Pirk, Christian W. W.; Blacquière, Tjeerd (Frontiers in Ecology and Evolution, 2022)
Many parts of the globe experience severe losses and fragmentation of habitats, affecting the self-sustainability of pollinator populations. A number of bee species coexist as wild and managed populations. Using honey bees as an example, we argue that several management practices in beekeeping threaten genetic diversity in both wild and managed populations, and drive population decline. Large-scale movement of hive stocks, introductions into new areas, breeding programs and trading of queens contribute to reducing genetic diversity, as recent research demonstrated for wild and managed honey bees within a few decades. Examples of the effects of domestication in other organisms show losses of both genetic diversity and fitness functions. Cases of natural selection and feralization resulted in maintenance of a higher genetic diversity, including in a Varroa destructor surviving population of honey bees. To protect the genetic diversity of honey bee populations, exchange between regions should be avoided. The proposed solution to selectively breed all local subspecies for a use in beekeeping would reduce the genetic diversity of each, and not address the value of the genetic diversity present in hybridized populations. The protection of Apis mellifera’s, Apis cerana’s and Apis koschevnikovi’s genetic diversities could be based on natural selection. In beekeeping, it implies to not selectively breed but to leave the choice of the next generation of queens to the colonies, as in nature. Wild populations surrounded by beekeeping activity could be preserved by allowing Darwinian beekeeping in a buffer zone between the wild and regular beekeeping area.